Features of microsporidia Nosema apis and Nosema ceranae (Nosema species) development of winter bee (Apis mellifera L.) generation - Odnosum, Hanna; Yefimenko, Tetiana (ScienceRise: Biological Science, 2022)
Temperature is one of the main abiotic factors affecting the development of causative agents of nosemosis in the bee’s body. The aim of the research. To determine the influence of the winter and summer bee nest temperature (20–22 °C and 35–36 °C, respectively) on the duration of Nosema species development of winter bee generation isolated in hoarding cages, and to trace the life cycle of Nosema species of bees with natural infection and overwintering in natural conditions, from November to the beginning of bee brood rearing (February). Materials and methods. For this, 200 bees Apis mellifera sossimai, selected from bee colony in November, were infected by syrup feeding containing Nosema species (5×104 spores per bee). Half of the bees were kept at 35–36 °C and half at 20–22 °C. The stages of Nosema species development were monitored daily for 13 days in midgut smears, stained according to Romanovsky-Giemsa (magnification 900x). Furthermore, with a 15 days frequency, from November to mid-February, 30 bees were selected from 20 bee colonies overwintered in natural conditions, and monitored the stages of Nosema species development at natural infection. Result. It was found that the Nosema species development of winter bee generation artificially infected by Nosema species, was suspended at meronts and sporonts stages until the 13th day from the moment of infection, regardless of the temperature at which the bees were kept in the experiment. In bees selected from bee colonies naturally infected with Nosema species prevailed meronts I, II and in an insignificant amount sporonts, until the end of December, active sporulation took place from the middle of January to the beginning of February. Conclusion. That is, the duration of the life cycle development of Nosema species depends little on temperature but is closely related to the life span of summer and winter bee generation and determined by the biochemistry of their relationships, which allow the parasite to save the host as its habitat